Using English Songs Minilyrics Collaboration To Improve Student's Pronunciation In LPKM Mitra English Course JatinomIn 2011/ 2012 Academic Year - Widayati, Arsida Sri (2012)
This research aims at knowing (1) the application of English songs MiniLyrics collaboration in teaching and learning pronunciation process, (2) describing English songs MiniLyrics collaboration improve student's pronunciation. This research was implemented in LPKM Mitra English Course Jatinom, at the beginner class using classroomaction research. The methods of collecting the data are observation, interview, documentation (examining), and test. The researcher taught English pronunciation using English songs MiniLyrics Collaboration. To analyze the data the researcher compared the results of pre-test and post-tests using descriptive comparative and critical analytic technique. English songs MiniLyrics collaboration was implemented in three cycles with each cycle consisting of four steps. By implementing English songs Minilyrics collaboration in teaching pronunciation, the students can pronounce English words better. The students' achievement of pronunciation is improved. It can be seen from the result of the students' activities during the action and the students' pronunciation achievement. The mean of pre-test is 58.90, post-test 100 and the improvement result of the implementation is 41.10%. The result of pretest and post- test showed the significant improvement. The chairman and English teacher said that this technique and media gave good effects in English learning. Most of the students said that they love this way. The students' motivated to practice easily learn English pronunciation. Thus, it enables them pronouncing the words correctly. Third, it has more strengths than it weaknesses. So, using English songs MiniLyrics collaboration is successful to improve the students's pronunciation.